EDUCATION AND TRAINING OF CHILDREN IN THE ERA OF NEW TECHNOLOGIES - I. V. Nekrasova (Science and Innovation Center Publishing House, 2020)
These are all issues that need to be discussed. The digital world is already around us, and it will stay with us. A new era has begun. We face a difficult task: to develop the principles of education of children in the age of the Internet. We need to think about everything and formulate a number of clear rules that will help in the education of children, as well as ensure their safety and health.